Development of excitation power-responsive anti-stokes emission wavelength switching and their energy saving induced by localized surface plasmon resonance - Jotaro Honda; Kosuke Sugawa; Koki Honma; Seiya Fukumura; Ryuzi Katoh; Hironobu Tahara; Joe Otsuki (Discover Nano, 2024)
Abstract We designed an external stimulus-responsive anti-Stokes emission switching using dual-annihilator-based triplet–triplet annihilation upconversion systems. This system, which was constructed by incorporating a palladium porphyrin derivative as a sensitizer and 9,10-diphenylanthracene (DPA) and 9,10-bis(triisopropylsilyl)ethynylanthracene (TIPS) as annihilators into polymer thin films, produced TIPS- and DPA-based anti-Stokes emission under low and high excitation powers, respectively. The mechanism involves the following: under low excitation power, triplet energy transfer from triplet-excited PdOEP to DPA is induced, followed by relay to TIPS. This results in the generation of triplet-excited TIPS, and the subsequent triplet–triplet annihilation between them produces TIPS-based anti-Stokes emission. Conversely, under high excitation power, the high-density triplet-excited DPA, generated through triplet energy transfer from PdOEP, undergoes triplet–triplet annihilation among themselves, resulting in the generation of DPA-based anti-Stokes emission. Additionally, we achieved energy savings by reducing the required excitation power for switching through the utilization of plasmonic metal nanoparticles. The strong local electromagnetic fields associated with the localized surface plasmon resonance of metal nanoparticles enhance the photoexcitation efficiency of PdOEP, subsequently increasing the density of triplet-excited DPA. As a result, anti-Stokes emission switching becomes feasible at lower excitation powers.